Investigation of the Relationship between Children's Prosocial Behaviour and Self-Regulation Skills - Kaya, İsa (Birleşik Dünya Yenilik Araştırma ve Yayıncılık Merkezi, 2020)
This study aimed to investigate the relationship between children's prosocial behavior and self-regulation skills. To collect the data of the study, demographic information form developed by the researcher was used for the demographic information of children, the prosocial behavior sub-dimension of the social behavior scale was used for the prosocial behavior, and the self-regulation skills scale was used for the self-regulation skills of the children. The collected data were analyzed by independent sample t-test, Pearson’s product moment correlation analysis and simple linear regression analysis in a computer package software. As a result of the research, while the self-regulation and prosocial behaviors of children differed according to gender and age of children, the situation of the children whether they have siblings and duration of the pre-school education did not make any significant difference. According to these results, girls' self-regulation and prosocial behavior scores were higher than that of boys and 6 years of age children’s scores were higher than that of 5 years of age children. While there was a moderate positive significant relationship between self-regulation skills and prosocial behavior, it was concluded that the prosocial behavior of children predicted self-regulation skills at the level of 11%.
Keywords: Prosocial Behavior; Self-Regulation Skills; Early Childhood; Preschool